Incremental innovation based on human capabilities. Empirical evidence on peruvian enterprises (Journal of Business, Universidad del Pacífico (Lima, Peru), 2011)
The achieved macroeconomic results by Peru in the past few years, make us anticipate a growth on business activities on the Topic of their capacities perspective in order to achieve advantage positions. However, this growth is based on, essentially, improved processes. Not perceiving a significant input from the enterprises to develop processes on radical or disruptive innovation, preferably approaching to incremental or low impact innovation processes. On the document's first part we will approach on the innovation subject as a competitive advantage factor based on an technological innovation capacity model. The second part presents an innovation model based on dynamics capacity. At least the document presents The methodology and results of the empirical study about the incremental innovation processes of the Peruvian enterprises.
Keywords: Innovation; incremental innovation; competitive advantage; innovation models; resources and capacity approach